2004
DOI: 10.1093/humrep/deh520
|View full text |Cite
|
Sign up to set email alerts
|

Oviduct prostacyclin functions as a paracrine factor to augment the development of embryos

Abstract: Mouse oviducts synthesized maximal PGI2 during day 2-3 p.c., coinciding with the transformation of 2-cell embryos to morulae. The results suggest that oviduct-derived PGI2 may enhance embryo development in a paracrine fashion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 14 publications
2
23
0
Order By: Relevance
“…These findings indicate that other factors must be involved in the upregulation during the estrous cycle, e.g., FSH or LH. Immunohistochemical studies in human (Huang et al 2002) and in mouse (Huang et al 2004) revealed that COX-1 was localized in the epithelial lining as well as in the smooth muscle cells, which is similar to our findings in the bovine oviduct.…”
Section: Discussionsupporting
confidence: 89%
“…These findings indicate that other factors must be involved in the upregulation during the estrous cycle, e.g., FSH or LH. Immunohistochemical studies in human (Huang et al 2002) and in mouse (Huang et al 2004) revealed that COX-1 was localized in the epithelial lining as well as in the smooth muscle cells, which is similar to our findings in the bovine oviduct.…”
Section: Discussionsupporting
confidence: 89%
“…The levels of PGE 2 and PGI 2 increase in the fallopian tubes (oviduct) following pregnancy, and these 2 prostaglandins, also produced in embryos, enhance embryo cell numbers, hatching, and implantation [77][78][79][80][81][82][83]. PGE 2 was found to have a positive affect on the growth of hematopoietic stem cell progenitors obtained from zebrafish and mouse embryonic stem cells [84].…”
Section: Discussionmentioning
confidence: 96%
“…COX-2 gene deficiency causes multiple defects in female reproduction (12); COX-2-derived PGI 2 is critical for embryo development from oviduct dilation to facilitation of embryo transfer (43), to embryo hatching (44) and implantation and decidualization through a non-PGI 2 receptor pathway (45,46). Reproductive capability in female COX-1 Ͼ COX-2 mice was partially, but not completely, rescued by targeted COX-1 exchange, which further confirms that the two isoforms are not completely functionally interchangeable.…”
Section: Discussionmentioning
confidence: 99%